A Six Sigma DMAIC Process for Supplier Performance Evaluation using AHP and Kano's Model - (:unkn) unknown (IGI GLOBAL, 2017)
The suppliers, which are one of the most important actors in the supply chain, have a significant effect on the performances of their customer firms. Hence, supplier performance evaluation has become a competitive tool in today's goods and service producing industries. This paper presents a supplier performance evaluation process developed using the Six Sigma Define - Measure - Analyse - Improve - Control (DMAIC) methodology. The proposed process has been applied in a central services company, where the suppliers had never been evaluated before. To this end, first of all, the evaluation criteria have been defined through brainstorming and meetings within the company, then weighted with Analytical Hierarchy Process (AHP), and categorized according to Kano's Model. Afterwards, suppliers have been scored and classified based on a proposed methodology using a modified version of Kano's model, and thus, the proposed process has proven to be useful in real life industrial applications.
Keywords: AHP; Kano's Model; Six Sigma DMAIC; Supplier Performance Evaluation; GREY RELATIONAL ANALYSIS; ANALYTIC NETWORK PROCESS; MULTI CRITERIA APPROACH; GOAL PROGRAMMING-MODEL; BOTTOM-LINE APPROACH; SIX-SIGMA; QUALITY MANAGEMENT; SELECTION PROBLEM; CONTINUOUS IMPROVEMENT; CHAIN